Design and Experiment of End-effectors for Picking Navel Oranges Based on the Underactuated Principle - Jiang Yanhong; Liu Jing; Hu Zhikui; Zhang Wan (Jixie chuandong)
The end-effector of fruit and vegetable picking robots is an important part of the picking robot, which directly affects the success rate and efficiency of picking. By analyzing the characteristics of navel oranges and based on the underactuated principle, a clamping end-effector for picking navel oranges is designed. The overall mechanism is composed of a two-layer and three-finger mechanical claw. One of the two layers of fingers is the carrier of the shearing mechanism, the other layer is the clamping finger for grasping the fruit, and the shearing mechanism is composed of a rocker slider mechanism. By building the mechanical model of the shear mechanism and the manipulator, the relevant parts are designed and selected according to the requirements. The motion error range of the shear mechanism is determined to prevent the interference of the manipulator. The finite element analysis on the key force parts is carried out, and the motion error caused by the deformation of the key force points is analyzed within the safety error range. The kinematic simulation of the end-effector is carried out by Adams software, and the results prove the feasibility of the end-effector. Finally, the picking and shearing test of navel oranges by the end-effector prototype shows that the overall picking success rate of the mechanism is 95%, and the picking cycle is 4.3 s.